2015
DOI: 10.2138/am-2015-4934ccbyncnd
|View full text |Cite
|
Sign up to set email alerts
|

Magmatic volatiles (H, C, N, F, S, Cl) in the lunar mantle, crust, and regolith: Abundances, distributions, processes, and reservoirs

Abstract: Many studies exist on magmatic volatiles (H, C, N, F, S, Cl) in and on the Moon, within the last several years, that have cast into question the post-Apollo view of lunar formation, the distribution and sources of volatiles in the Earth-Moon system, and the thermal and magmatic evolution of the Moon. However, these recent observations are not the first data on lunar volatiles. When Apollo samples were first returned, substantial efforts were made to understand volatile elements, and a wealth of data regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
106
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(126 citation statements)
references
References 296 publications
(589 reference statements)
18
106
1
Order By: Relevance
“…Several authors have suggested that H 2 dissolution could be important in the eruptive products of planetary bodies, including the Moon, that are more reduced than the Earth (Zhang and Ni 2010;ElkinsTanton and Grove 2011;Zhang 2011;Sharp et al 2013;McCubbin et al 2015). However, extrapolation (from 0.7-3 GPa) to low pressures of recent experimental data on the solubility of H 2 in basaltic melts (Hirschmann et al 2012) suggests that basaltic melt in equilibrium with 1 atm of pure H 2 likely contains only ~0.4 ppm (by weight) dissolved molecular hydrogen.…”
Section: The Potential Role Of Other H-bearing Species In Lunar Meltsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several authors have suggested that H 2 dissolution could be important in the eruptive products of planetary bodies, including the Moon, that are more reduced than the Earth (Zhang and Ni 2010;ElkinsTanton and Grove 2011;Zhang 2011;Sharp et al 2013;McCubbin et al 2015). However, extrapolation (from 0.7-3 GPa) to low pressures of recent experimental data on the solubility of H 2 in basaltic melts (Hirschmann et al 2012) suggests that basaltic melt in equilibrium with 1 atm of pure H 2 likely contains only ~0.4 ppm (by weight) dissolved molecular hydrogen.…”
Section: The Potential Role Of Other H-bearing Species In Lunar Meltsmentioning
confidence: 99%
“…1978; Fogel and Rutherford 1995;Nicholis and Rutherford 2009;Rutherford and Papale 2009;Wetzel et al 2015), and others have proposed H 2 (Sharp et al 2013;McCubbin et al 2015). Arguments in support of CO as the primary propellant hinge on the H-depleted nature of lunar magmas compared to most terrestrial magmas (Saal et al 2008;Hauri et al 2011;Wetzel et al 2015;Chen et al 2015) and on the presence of Fe metal blebs in erupted lunar melts, thought to be the result of the reduction of FeO in the melt in response to graphite oxidation to CO during magma ascent (e.g., Nicholis and Rutherford 2009).…”
Section: Which Volatile Species Likely Dominated In the Vapor That Drmentioning
confidence: 99%
See 2 more Smart Citations
“…chondritic) asteroid sourced impactors (Day and Walker 2015). These impactors could also have contributed to the Moon's volatile and moderately volatile element budget and isotopic signature (McCubbin et al 2015;Tartèse 2016) (although degassing of the magma ocean may have contributed to some later depletion of volatile species Kato et al 2015). Examination of the lunar rock hydrogen and nitrogen isotope records indicate that the sources of impactors that delivered such volatiles to the lunar magma ocean were dominated by water or ice-rich carbonaceous chondrite-like asteroid projectiles (Barnes et al 2016).…”
Section: Late Accretionmentioning
confidence: 99%